Origins of Enterovirus Replication Organelles Established by Whole-Cell Electron Microscopy - Melia, Charlotte E. (mBio, 2019)
Enterovirus genome replication occurs at virus-induced structures derived from cellular membranes and lipids. However, the origin of these replication organelles (ROs) remains uncertain. Ultrastructural evidence of the membrane donor is lacking, suggesting that the sites of its transition into ROs are rare or fleeting. To overcome this challenge, we combined live-cell imaging and serial block-face scanning electron microscopy of whole cells to capture emerging enterovirus ROs. The first foci of fluorescently labeled viral protein correlated with ROs connected to the endoplasmic reticulum (ER) and preceded the appearance of ROs stemming from the trans-Golgi network. Whole-cell data sets further revealed striking contact regions between ROs and lipid droplets that may represent a route for lipid shuttling to facilitate RO proliferation and genome replication. Our data provide direct evidence that enteroviruses use ER and then Golgi membranes to initiate RO formation, demonstrating the remarkable flexibility with which enteroviruses usurp cellular organelles.